210Po in Pacific Salmon From the West Coast of Canada and Its Contribution to Dose by Ingestion. Issue 3 (September 2019) - Chen, J.; Cooke, M.W.; Mercier, J.F.; Trudel, M.; Kellogg, J.; Cullen, J.T.
Abstract : Abstract: In response to public concern in Canada regarding health impacts attributable to the Fukushima Daiichi nuclear accident, oceanic seawater samples from the north Pacific and Arctic oceans, coastal seawater samples from 16 locations along the British Columbia coastline, and seafood samples (salmon, steelhead trout, and shellfish) from British Columbia coastal waters were collected and analyzed. This paper reports radiological analysis results of Pacific salmon samples ( Oncorhynchus species) obtained from summer 2013 to fall 2016. While radioactive cesium from the Fukushima disaster was not detectable in most salmon samples, naturally occurring 210 Po was measured in almost all individual samples in varying activity concentrations, from below the detection limit of 0.2 Bq kg −1 fresh weight up to 4.7 Bq kg −1 fresh weight. The average 210 Po concentration among 297 salmon samples was 0.73 Bq kg −1 fresh weight. The average ingested radiation dose per kilogram of salmon from 210 Po is estimated to be 0.88 μSv, and the average dose from 137 Cs is estimated to be 0.0026 μSv. The annual dose from ingested salmon would be only a fraction of the worldwide average annual effective dose from exposure to natural background radiation (2, 400 μSv y −1 ) (UNSCEAR 2000 ). The measurement results showed clearly that radiation doses to people consuming fish (such as salmon) from the Canadian west coast pose no health concern.